2016
DOI: 10.1016/j.zool.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in hair cortisol in wild and captive non-human primates

Abstract: Hair cortisol analysis is a potentially powerful tool for evaluating adrenal function and chronic stress. However, the technique has only recently been applied widely to studies of wildlife, including primates, and there are numerous practical and technical factors that should be considered to ensure good quality data and the validity of results and conclusions. Here we report on various intrinsic and extrinsic sources of variation in hair cortisol measurements in wild and captive primates. Hair samples from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…The interest in hair as a record of endocrine activity derives from the various unique features of hair compared to more traditional substrates (e.g., blood, stool, urine, saliva), that offer advantages to researchers interested in using cortisol levels as a proxy for chronic stress (Fourie et al 2016). Cortisol is incorporated into the hair shaft through two principal mechanisms.…”
Section: Cortisol In Hairmentioning
confidence: 99%
“…The interest in hair as a record of endocrine activity derives from the various unique features of hair compared to more traditional substrates (e.g., blood, stool, urine, saliva), that offer advantages to researchers interested in using cortisol levels as a proxy for chronic stress (Fourie et al 2016). Cortisol is incorporated into the hair shaft through two principal mechanisms.…”
Section: Cortisol In Hairmentioning
confidence: 99%
“…The application of hair steroid hormone profiles in wildlife management, conservation and research must be supported by requisite validation studies (Heistermann, 2010; Fourie et al ., 2016). Otherwise, the results and conclusions drawn from such usages are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we found that the CORT concentrations were widely variable within this natural population (>200-fold differences after handling), as well as finding significant variability in the baseline data (nearly a 50-fold range). Some variation is expected between age classes, because CORT has been shown to decrease with age in several taxa (Fourie and Bernstein 2011; Fourie et al ., 2016; Mateo, 2006). This juvenile-associated high is generally attributed to mobilization of glucose for facilitation of growth and energy storage, as well as to rapidly promote memory, learning, and survival behaviours (e.g.…”
Section: Discussionmentioning
confidence: 99%